Cold gas studies of a z = 2.5 protocluster. Issue Volume 15:Issue S359(2020) (March 2019) - Lee, Minju M.; Tanaka, Ichi; Kawabe, Rohei
Abstract: We present studies of a protocluster at z =2.5, an overdense region found close to a radio galaxy, 4C 23.56, using ALMA. We observed 1.1 mm continuum, two CO lines (CO (4–3) and CO (3–2)) and the lower atomic carbon line transition ([CI ]( 3 P1 - 3 P0 )) at a few kpc (0″.3-0″.9) resolution. The primary targets are 25 star-forming galaxies selected as H α emitters (HAEs) that are identified with a narrow band filter. These are massive galaxies with stellar masses of > 10 10 M ʘ that are mostly on the galaxy main sequence at z =2.5. We measure the molecular gas mass from the independent gas tracers of 1.1 mm, CO (3–2) and [CI ], and investigate the gas kinematics of galaxies from CO (4–3). Molecular gas masses from the different measurements are consistent with each other for detection, with a gas fraction ( f gas = M gas /( M gas + M star )) of ≃ 0.5 on average but with a caveat. On the other hand, the CO line widths of the protocluster galaxies are typically broader by ˜50% compared to field galaxies, which can be attributed to more frequent, unresolved gas-rich mergers and/or smaller sizes than field galaxies, supported by our high-resolution images and a kinematic model fit of one of the galaxies. We discuss the expected scenario of galaxy evolution in protoclusters at high redshift but future large surveys are needed to get a more general view.